Protective efficacy of vitamin b12 combined with far-infrared radiation on radiation-induced skin damage in the treatment of pelvic tumours. (2015) - Ge, Qin, Cen-ming Yu, Jing Cai, Chun-xia Chu, Guo-dong Xie; Zhao, Ji-Zhong
No abstract available